The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1105/tpc.5.9.1089
|View full text |Cite
|
Sign up to set email alerts
|

Fungal Elicitor-Induced Bean Proline-Rich Protein mRNA Down-Regulation Is Due to Destabilization That Is Transcription and Translation Dependent.

Abstract: In bean cells treated with fungal elicitor, the transcripts of PwPRPí, a gene encoding a proline-rich protein, decreased to -6% of the original level within 4 hr. The apparent mRNA half-life during the period of rapid degradation was -45 min. The rate of PwPRPí gene transcription remained constant over this period, as determined by nuclear run-off assays, indicating a decrease in mRNA stability. By using actinomycin D to block transcription, the half-life of PwPRPl mRNA in unelicited cells was estimated to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 45 publications
2
47
0
Order By: Relevance
“…The authors hypothesized that this likely cell wall protein is reduced because of its low Tyr content and therefore its low potential for wall strengthening during the defense response (Sheng et al, 1991). The decrease in the PvPRP1 mRNA level in cells treated with elicitors was demonstrated to be due to destabilization, which is dependent on the synthesis of new RNA and protein (Zhang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…The authors hypothesized that this likely cell wall protein is reduced because of its low Tyr content and therefore its low potential for wall strengthening during the defense response (Sheng et al, 1991). The decrease in the PvPRP1 mRNA level in cells treated with elicitors was demonstrated to be due to destabilization, which is dependent on the synthesis of new RNA and protein (Zhang et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no precedence for mRNA turnover as a regulatory step for GS in bacteria, regulation through differential stability of the same mRNA under different growth conditions is well documented in eukaryotic cells (Atwater et al, 1990;Brodl and Ho, 1991;Zhang et al, 1993). Analysis of Arabidopsis mutants that overaccumulate soluble Met revealed that the gene for cystathionine ␥-synthase, the key enzyme in Met biosynthesis, is regulated at the level of mRNA stability (Chiba et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…1). In addition, AOS may regulate the stability of defense-related "As (Zhang et al, 1993). Treatment of bean :e11 suspensions with H202 induced the accumulation of mRNAs encoding Phe ammonia-lyase, chalcone synthase, and chalcone isomerase (enzymes required for phytoalexin biosynthesis) and a baisic endochitinase, whereas a mRNA encoding a Prorich protein was degraded (Y. Sharma, K. Sathasivan, N. Bays, and M.C.…”
Section: Roles Of Aos In Plant Defensementioning
confidence: 99%